Outlier Analysis of the Modified Gompertz Model used for Modelling the Growth of Callus Cultures from Glycine wightii (Wight & Arn.) Verdc. (Asian Journal of Plant Biology, 2015)
The production of callus and cell culture can be an important tool to study plant regulation, biosynthesis and biochemistry. Previously, we model the growth of growth of Glycine wightii published literature to obtain vital growth constants. We discovered that the modified Gompertz model was the best model based on statistical test such as root-mean-square error (RMSE), adjusted coefficient of determination (R2), bias factor (BF), accuracy factor (AF) and corrected AICc (Akaike Information Criterion) to explain the callus growth. However, the use of statistical tests to choose the best model relies heavily on the residuals of the curve to be statistically robust. Usually, the residuals need be tested for the occurrence of outliers (at 95 or 99% of confidence). In this work, the Grubbâ€™s test to detect the presence of outlier in the growth model was carried out. The results showed that there was no outlier present, and the modified Gompertzmodel was adequate to model the callus growth.
Keywords: Glycine wightii, callus growth, modified Gompertz model, least square method, Grubbs test